2016
DOI: 10.1007/s10072-016-2558-1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and long-term outcome of tumefactive demyelinating lesions in multiple sclerosis

Abstract: Although tumefactive multiple sclerosis is a well recognized variant of multiple sclerosis, prognostic uncertainty still exists about long term prognosis. The aim of this study was to estimate the occurrence and long term outcome of tumefactive demyelinating lesions (TDLs) in a cohort of multiple sclerosis patients. We reviewed brain MRI of 443 patients referred to our MS clinic. All patients meeting the McDonald criteria for multiple sclerosis and showing at least one TDL were included. Kaplan-Meier estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…It has been said that once TDLs relapses happen, their disease progression was identical to that of traditional relapsing-remitting MS ( 6 ). However, only 27.6% of patients in our study ended up in the MS group, which was somewhat different from prior studies ( 19 , 20 ). We classified the etiology of patients with TDLs into six categories: MS, NMOSD, MOGAD, Balo, ADEM, and the other etiology, which is more precise than previous studies, and some subsets might be associated with MS, possibly resulting in a relative decrease in the number of patients in the MS group.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been said that once TDLs relapses happen, their disease progression was identical to that of traditional relapsing-remitting MS ( 6 ). However, only 27.6% of patients in our study ended up in the MS group, which was somewhat different from prior studies ( 19 , 20 ). We classified the etiology of patients with TDLs into six categories: MS, NMOSD, MOGAD, Balo, ADEM, and the other etiology, which is more precise than previous studies, and some subsets might be associated with MS, possibly resulting in a relative decrease in the number of patients in the MS group.…”
Section: Discussioncontrasting
confidence: 99%
“…4,13 Our study identified 24 tumefactive lesions in 293 MS patients (8.21%), a higher proportion than the previous estimate of 0.1%-0.2% of MS patients. 23 However, the higher percentage may be explained by the many MR studies carried out in our MS patients and the high quality currently offered by this technique compared to the past. The true incidence of tumefactive lesions is unknown and Poser's results 24,25 are probably an underestimation.…”
Section: Discussionmentioning
confidence: 95%
“…Pathological changes associated with the formation of new inflammatory MS lesions are difficult to study, because such lesions are rarely fatal. Two main strategies can be pursued to understand underlying mechanisms of MS lesion formation: (i) To describe pathological findings in patients who died relatively early after the onset of a new symptomatic lesion, or (ii) to investigate brain biopsies of patients diagnosed with tumefactive MS, also called "pseudotumoral MS", a well-recognized variant of MS (Hardy, Tobin et al 2016, Totaro, Di Carmine et al 2016. Following the first approach, Barnett and Prineas reported that the earliest pathological changes, described as prephagocytic lesions, consist of oligodendrocyte apoptosis and microglial activation associated with few lymphocytes and phagocytes in regions of relative myelin preservation.…”
Section: Discussionmentioning
confidence: 99%